Ukraine's Trade Policy : A Strategy for Integration into Global Trade - World Bank (Washington, DC, 2012)
This publication identifies the key drivers of Ukraine's recent trade performance, assesses current trade policies, and proposes recommendations to strengthen the Ukraine's trade integration strategy. It also identifies core bottlenecks in the ongoing integration processes, including global and regional integration. The study concludes that the main obstacles to furthering Ukraine's trade integration are domestic, and relate to deficiencies in the business environment. Problems in customs administration, standardization, and administrative barriers for new entry require immediate attention. The report highlights specific policy issues that hamper World Trade Organization (WTO) accession, such as trade legislation, protection of intellectual property rights, government support for specific industries, and export restrictions. It also recommends improvements in the structure of Ukraine's import tariffs, reform of both the regime of free economic zones and mechanism of the value-added tax (VAT) refund, and investment in a major upgrade of government capacity for investment and export promotion. The report also draws attention to the importance of the post-WTO accession agenda for Ukraine. To take advantage of WTO membership, the Government will need to undertake significant institutional reforms to implement WTO regulatory rules in ways that facilitate integration into the world economy and provide benefits to private sector participants.